1989
DOI: 10.1093/oxfordjournals.humrep.a136920
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal hysterosalpingo-contrast-sonography (Hy-Co-Sy) compared with conventional tubal diagnostics

Abstract: Transvaginal hysterosalpingo-contrast-sonography (Hy-Co-Sy) is described as a new method for direct imaging of the tubal passage in tubal diagnostics. During one period of anaesthesia, a transvaginal Hy-Co-Sy was followed by either hysterosalpingography or chromolaparoscopy in 42 patients with sterility disorders. The contrast-enhanced sonography of the tubes was performed in eight cases with sterile saline solution (group 1) and 34 cases with a specially developed ultrasound contrast medium (SH U 454, group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 0 publications
2
37
0
3
Order By: Relevance
“…However they did not focus on the evaluation of tubal patency. Other authors have also demonstrated that the 'sonohysterography' using hyporeflective contrast media shows results that are comparable to the hysteroscopy concerning the evaluation of uterine findings (Deichert et al, 1989(Deichert et al, , 1993Cicinelli et al, 1995). Beyond that, contrast-enhanced sonography allows an overall evaluation of the uterus.…”
Section: Thomas Strowitzkimentioning
confidence: 88%
See 1 more Smart Citation
“…However they did not focus on the evaluation of tubal patency. Other authors have also demonstrated that the 'sonohysterography' using hyporeflective contrast media shows results that are comparable to the hysteroscopy concerning the evaluation of uterine findings (Deichert et al, 1989(Deichert et al, , 1993Cicinelli et al, 1995). Beyond that, contrast-enhanced sonography allows an overall evaluation of the uterus.…”
Section: Thomas Strowitzkimentioning
confidence: 88%
“…The use of hyper-reflective contrast media (e.g. Echovist®, Schering AG; Müllerstrasse 178, 13353 Berlin) easily allows the demonstration of the tubal patency of each individual Fallopian tube by detection of a 'flow phenomenon' of the contrast dye (Deichert et al, 1989(Deichert et al, , 1993. A meta-analysis of three comparative studies with a total of 1007 patients was able to confirm these results (Holz et al, 1997).…”
Section: Thomas Strowitzkimentioning
confidence: 99%
“…Deichert et al (5) used transvaginal hysterocontrastsonography. The tubes were visualized by isotonic saline and /or contrast medium SHU454.…”
Section: Discussionmentioning
confidence: 99%
“…1989-ben Deichert és Schlief használt először kontrasztanyaggal erősített transvaginalis ultrahangvizsgálatot a petevezeték átjárhatóságának megítélésére [12]. A hisztero-kontraszt-szalpingográfia (hystero-contrast-sonography -HyCoSy) eljárással viszonylag gyorsan és egyszerűen vizsgálhatjuk a méh üregét és a petevezetékek átjárhatóságát.…”
Section: Hisztero-kontraszt-szalpingográfiaunclassified